PERAN ORANG TUA DAN KEM AMPUAN TOILET TRAINING PADA ANAK USIA DINI (18 – 36 BULAN) - Siska Iskandar; Maritta Sari (Sekolah Tinggi Ilmu Kesehatan Tri Mandiri Sakti Bengkulu, 2017)
Toilet training is one of the efforts to train children to control and urinate and water. This study aims to determine the relationship of the role of parents with the ability of toilet training in early childhood (18-36 months). This research was conducted in PAUD Alam Ceria Bengkulu City in September 2017. The methods of this observational study. The population in this study is the mother of children aged 18-36 months. The results showed that the independent variables that had an influence on the ability of toilet training were parents role variable (87,5%) less good and (31,8%) good. The result of bivariate analysis using chi square found that there was a relationship between the role of parents with the ability of toilet training of early childhood (P = 0.000). The role of parents resulted in a 2.7 times risk of early childhood toilet training capability (RP = 2.7). The researcher suggested to the instructor to always give good role by conducting toilet training program toilet to the child and to parents can give information to parent about how to do parent role in train children toilet training at home. Keywords : children, role of parent, toilet training